To solve an equation for an unknown value,

keep the equation

balanced while

isolating the unknown.

First, divide both sides of the equation by 6.

Then, subtract 4.2 from both sides of the equation.

6(*x* + 4.2) | = | 36 |

6(*x* + 4.2) ÷ 6 | = | 36 ÷ 6 |

*x* + 4.2 | = | 6 |

*x* + 4.2 - 4.2 | = | 6 - 4.2 |

*x* | = | 1.8 |

First, add 10 to both sides of the equation.

Then, divide both sides of the equation by -5.

-5*x* - 10 | = | -15 |

-5*x* - 10 + 10 | = | -15 + 10 |

-5*x* | = | -5 |

-5*x* ÷ -5 | = | -5 ÷ -5 |

*x* | = | 1 |

First, subtract 0.7 from both sides of the equation.

Then, divide both sides of the equation by 2.1.

2.1*x* + 0.7 | = | 7 |

2.1*x* + 0.7 - 0.7 | = | 7 - 0.7 |

2.1*x* | = | 6.3 |

2.1*x* ÷ 2.1 | = | 6.3 ÷ 2.1 |

*x* | = | 3 |